Investigating factors influencing overweight and obesity among adult households in Ethiopia: a multilevel ordered analysis of 2016 EDHS data - Deressa, Alemayehu; Firdisa, Dawit; Birhanu, Abdi; Debella, Adera; Gamachu, Mulugeta; Eyeberu, Addis; Dechasa, Deribe Bekele; Jibro, Usmael; Balis, Bikila; Tolera, Moti; Regassa, Lemma Demissie; Mussa, Ibsa (Frontiers in Endocrinology, 2024)
Background In both high- and low-income countries, including Ethiopia, overweight and obesity have emerged as public health issues of the 21st century. Hence, obtaining conclusive evidence concerning the factors that influence adults’ body mass index is important. Therefore, using representative data, our study sought to provide solid evidence on factors influencing overweight and obesity among adults in Ethiopia. Methods The 2016 Ethiopia Demographic and Health Survey (EDHS), a dataset composed of a nationally representative sample of the survey, served as the basis for the study. Both descriptive and analytic findings were produced using STATA version 14. The data collection were conducted from January to June 2016. A total sample of 39,749 adults, 18 years and older, were included. Predictors were assessed using multivariable ordinal logistic regression analysis, and the results were presented as an adjusted proportional ratio (POR) with a 95% confidence interval. Statistical significance was declared at a p-value of <0.05. Results Overall, the magnitude of overweight and obesity among adults in Ethiopia was 8.5% (95% CI: 8.2% to 8.7%) and 2.9% (95% CI: 2.7% to 3.1%), respectively. Predictor variables such as smoking (POR = 0.53, 95% CI: 0.42–0.67); being female (POR = 1.21, 95% CI: 1.13–1.30); being married (POR = 1.91, 95% CI: 1.26–2.90); having a secondary education (POR = 1.42, 95% CI: 2.23–1.64); having a diploma and above education (POR = 1.78, 95% CI: 1.44–2.21); having a poorer (POR = 1.22, 95% CI: 1.13–1.31), middle (POR = 1.30, 95% CI: 1.20–1.40), richer (POR = 1.35, 95% CI: 1.25–1.47), and richest (POR = 3.13, 95% CI: 2.79–3.51) wealth index rating; and having a rural residence (POR = 0.48, 95% CI: 0.43–0.54) were significantly associated with overweight and obesity. Conclusions Overall, 8.5% and 2.9% of Ethiopian adults were overweight and obese, respectively. Factors such as smoking, sex, marital status, educational status, wealth index, residence, and region were significantly associated with overweight and obesity among adult households. As a result, enhancing lifestyle modifications is enormous, and it is necessary to have more tangible evidence concerning the factors influencing body mass index utilizing more representative data from local and global.